Developments in 3D Geo-Information Sciences - Neutens, Tijs.; Maeyer, Philippe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book covers various aspects of 3D geoinformation regarding data acquisition, modeling, analysis, management, visualization and technology. In recent years, a wide range of 3D models have been developed including voxels, tetrahedral networks (TEN), constructive solid geometry (CSG) and boundary representation (B-rep), and new data collection techniques have emerged, such as mobile mapping and laser scanning. In light of these developments, this book brings together some of the latest achievements in the realm of 3D geoinformation. It comprises a selection of high-quality papers that were presented at the 4th International Workshop on 3D geoinformation. The book is aimed at a broad range of academics and practitioners interested in the 3D component of geographical information science including GIscientists, land surveyors, computer engineers, photogrammetrists, urban planners, archaeologists and cartographers.
Euler Operators and Navigation of Multi-shell Building Models -- True-3D Visualization of Glacier Retreat in the Dachstein Massif, Austria: Cross-Media Hard- and Softcopy Displays -- Towards Advanced and Interactive Web Perspective View Services -- Interactive modelling of buildings in Google Earth: A 3D tool for Urban Planning -- An Experimentation of Expert Systems Applied to 3D Geological Models Construction -- Data validation in 3D cadastre -- From Three-Dimensional Topological Relations to Contact Relations -- Needs and potential of 3D city information and sensor fusion technologies for vehicle positioning in urban environments -- Modeling Visibility through Visual Landmarks in 3D Navigation using Geo-DBMS -- A 3D inclusion test on large dataset -- 3D Volumetric Soft Geo-objects for Dynamic Urban Runoff Modeling.
Keywords: Geography; Geographical information systems; Geography; Geographical Information Systems/Cartography.